2008
DOI: 10.1111/j.1365-2214.2008.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsive parenting is associated with improved type 1 diabetes‐related quality of life

Abstract: Background-Improved quality of life is an important treatment goal for children and adolescents with type 1 diabetes. While previous research supports a relationship between family environment and quality of life, little research has addressed the relationship of parenting style constructs to quality of life in children with chronic disease. The present investigation assesses the relationship of parent responsiveness and demandingness with diabetes-related quality of life among children and adolescents with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 39 publications
(78 reference statements)
0
57
0
3
Order By: Relevance
“…Furthermore, it is believed that some negative aspects of parenting style are subject to a social desirability bias (Botello-Harbaum, Nansel, Haynie, Iannotti, & Simons-Morton, 2008;Kaufmann et al, 2000). Multi-informant reporting may help to overcome some of the bias involved in single-informant studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is believed that some negative aspects of parenting style are subject to a social desirability bias (Botello-Harbaum, Nansel, Haynie, Iannotti, & Simons-Morton, 2008;Kaufmann et al, 2000). Multi-informant reporting may help to overcome some of the bias involved in single-informant studies.…”
Section: Discussionmentioning
confidence: 99%
“…An emotionally supportive and accepting parenting style (parental responsiveness) is well-documented as having enduring implications in improved quality of life for children and adolescents with T1D [13]. In a sample of 81 adolescents with T1D and their parents, Botello-Harbaum and colleagues [13] found that over a 12-month period, parental responsiveness continued to promote greater self-reported quality of life in their child.…”
Section: Introductionmentioning
confidence: 99%
“…An American study showed that adolescents with chronic diseases who spent more of their treatment time supervised by parents, particularly mothers, had better adherence,15 and likewise, a review on the role of parental involvement in diabetes management suggested that a premature withdrawal of parental involvement is associated with poor diabetes outcomes, whereas continued parental support and monitoring is associated with better outcomes among adolescents 16. Furthermore, a study of adolescents with type 1 diabetes reported that a supportive and emotionally warm parenting style (authoritative parenting style) promoted improved quality of life 17. However, a study on sickle-cell disorder and thalassemia found that adolescents often feel that parents are so concerned about the illness that they focus on the illness at the expense of the adolescent as an individual person 18…”
Section: Introductionmentioning
confidence: 99%